Conceptualizing Senior Tourism Behaviour: A Life Events Approach. (December 2019) - Huber, Dominik; Milne, Simon; Hyde, Kenneth F
This article utilizes the context of senior tourism to conceptualize life events and their impacts on tourism behaviour. Life events are markers in the individual life course that can be used to explain the formation of travel patterns. This study adopts a qualitative biographical research methodology to explore the life trajectories and related tourism behaviours of 23 senior citizens in Freising, Germany, to gain an in-depth understanding of how and why tourism behaviour changes across the individual life course. Life events can have a strong impact on tourism behaviour; they can interrupt existing travel patterns or prompt new ones. Life events and their theoretical underpinnings form a largely untouched field in the domain of tourism and represent an area worthy of more extensive research. A better understanding of life events as they relate to tourism behaviours presents opportunities for the tourism industry to develop and design custom-tailored products and services.